3, 5-dibromo-4-hydroxybenzaldehyde dissolved in aqueous solutions of ethanol, n-propanol, acetonitrile and N, N-dimethylformamide: Solubility modelling, solvent effect and preferential solvation investigation. (December 2020) - Zhu, Changfei; Xu, Renjie; Yin, Hao; Zhao, Hongkun; Farajtabar, Ali
Graphic abstract: Highlights: 3, 5-Dibromo-4-hydroxybenzaldehyde solubility in four aqueous mixtures was determined. Solubility was correlated by Jouyban-Acree, Apelblat-Jouyban-Acree and van't Hoff-Jouyban-Acree models. Preferential solvation of 3, 5-dibromo-4-hydroxybenzaldehyde in four mixtures were derived via IKBIs method. Cavity formation energy of solvents played a significant role on solubility variation. Abstract: Equilibrium solubility of 3, 5-dibromo-4-hydroxybenzaldehyde in four aqueous solutions of ethanol/ n -propanol/acetonitrile/ N, N -dimethylformamide (DMF) was determined at temperatures covering from 278.15 K to 323.15 K. All determinations were carried out by the well-known saturation shake-flask method under atmospheric pressure of 101.2 kPa. The maximum values of solubility data appeared in neat ethanol/ n -propanol/acetonitrile/DMF for each solution. By Jouyban-Acree model, Apelblat-Jouyban-Acree model and van't Hoff-Jouyban-Acree model, the 3, 5-dibromo-4-hydroxybenzaldehyde solubility was well mathematically described obtaining RAD values smaller than 3.71% and RMSD values smaller than 2.27 × 10 -4 . The Kamlet and Taft linear solvation energy relationships were employed to examine the chief factors describing solvent effect. The cavity formation energy of solvents played a significant role on the solubility variation of 3, 5-dibromo-4-hydroxybenzaldehyde in different aqueous solutions. The local mole fractions of ethanol/ n -propanol/acetonitrile/DMF and water molecules around the 3, 5-dibromo-4-hydroxybenzaldehyde molecule were quantitatively studied via the Inverse Kirkwood–Buff integrals way used to the solubility values. 3, 5-Bibromo-4-hydroxybenzaldehyde was preferentially solvated by water in water-rich compositions for the ethanol/ n -propanol/acetonitrile/DMF + water mixtures; while within co-solvent-rich and intermediate compositions, 3, 5-dibromo-4-hydroxybenzaldehyde was preferentially solvated by ethanol/ n -propanol/acetonitrile/DMF.